Selective autophagy and viruses - Sumpter, Rhea (Landes Bioscience, 2011)
In recent years, the process of selective autophagy has received much attention with respect to the clearance of protein aggregates, damaged mitochondria and bacteria. However, until recently, there have been virtually no studies on the selective autophagy of viruses, although they are perhaps one of the most ubiquitous unwanted constituents in human cells. Recently, we have shown that the ability of neuronal Atg5 to protect against lethal Sindbis virus central nervous system (CNS) infection in mice is associated with impaired viral capsid clearance, increased p62 accumulation and increased neuronal cell death. In vitro, we showed that p62 interacts with the Sindbis capsid protein and targets it for degradation in autophagosomes. Herein, we review these findings and broadly speculate about potential roles of selective viral autophagy in the regulation of host immunity and viral pathogenesis.